Предмет: Алгебра,
автор: ksyunkasysoeva
Упростите выражение: m*(m-3)-(4-m^2) при=-1/10
Ответы
Автор ответа:
0
1) m*(m-3)=m (в квадрате)-3m
2)m^2-3m-4+m^2= -3m-4.
3) Если m=1/10, то
-3*(-1/10)=(-3)*(-0.1)=-0.3
2)m^2-3m-4+m^2= -3m-4.
3) Если m=1/10, то
-3*(-1/10)=(-3)*(-0.1)=-0.3
Похожие вопросы
Предмет: История,
автор: garushafrikyn597
Предмет: Другие предметы,
автор: 13anyutochka01
Предмет: История,
автор: bravelswiftkey
Предмет: Литература,
автор: Красивая111
Предмет: Алгебра,
автор: vkusnyasha